The the Complete Rust Programming Reference Guide: Design, Develop, and Deploy Effective Software Systems Using the Advanced Constructs of Rust - Sharma, Rahul; Kaihlavirta, Vesa; Matzinger, Claus (Learning path, 2019)
This Learning Path is your easy reference to mastering Rust programming. It begins with an introduction to Rust data structures and algorithms and covers the entire spectrum, including memory safety, type system, concurrency, and other features of Rust 2018.